Immunocytochemical study of the interaction of soybean trypsin inhibitor with rat intestinal mucosa. Issue 4 (April 1978) - Wilson, P A; Melmed, R N; Hampe, M M; Holt, S J
Abstract : To investigate further the cause of the pancreatic enlargment induced by orally ingested soybean trypsin inhibitor (STI), antibodies raised against STI and purified by affinity chromatography were used to localise dietary STI in the rat gut by fluorescent immunocytochemical methods. This technique permitted the clear intracellular demonstration of STI in the ileal mucosa of suckling rats. However, in adult rats no entry of STI into mucosal cells of the small intestine could be demonstrated, it being confined to the luminal surface of the mucosa. Although the passage of STI into and across the adult intestinal mucosa could not be excluded through the use of this technique, the results are consistent with an intraluminal mode of action of STI as suggested by Green and Lyman (1972)--namely, that the pancreatic enlargement caused in sensitive species results from the inhibition of trypsin (which acts as the physiological inhibitor of the mucosal secretion of pancreotrophic hormones), thus resulting in the uninhibited secretion of these hormones.